Commit 94651afe authored by simonpj's avatar simonpj
Browse files

Follow test output changes

parent 0d8e310a
annfail10.hs:9:11:
annfail10.hs:9:1:
Ambiguous type variable `a' in the constraints:
(Num a) arising from the literal `1' at annfail10.hs:9:11
(Data.Data.Data a) arising from an annotation
at annfail10.hs:9:1-15
(Num a) arising from the literal `1' at annfail10.hs:9:11
Probable fix: add a type signature that fixes these type variable(s)
In the expression: 1
In the annotation: {-# ANN f 1 #-}
TYPE SIGNATURES
emptyL :: forall a. ListColl a
test2 :: forall c a a1.
(Coll c, Elem c ~ (a, a1), Num a, Num a1) =>
(Num a1, Num a, Coll c, Elem c ~ (a, a1)) =>
c -> c
TYPE CONSTRUCTORS
data ListColl a
......
T4179.hs:26:16:
Could not deduce (DoC (x (A2 (FCon x) -> A3 (FCon x))))
from the context (Functor x, DoC (FCon x))
arising from a use of `op'
Possible fix:
add (DoC (x (A2 (FCon x) -> A3 (FCon x)))) to the context of
the type signature for `fCon'
or add an instance declaration for
(DoC (x (A2 (FCon x) -> A3 (FCon x))))
In the first argument of `foldDoC', namely `op'
In the expression: foldDoC op
In an equation for `fCon': fCon = foldDoC op
T4179.hs:26:16:
Could not deduce (A2 (x (A2 (FCon x) -> A3 (FCon x)))
~
......@@ -37,3 +24,17 @@ T4179.hs:26:16:
In the first argument of `foldDoC', namely `op'
In the expression: foldDoC op
In an equation for `fCon': fCon = foldDoC op
T4179.hs:26:16:
Could not deduce (DoC (x (A2 (FCon x) -> A3 (FCon x))))
from the context (Functor x, DoC (FCon x))
arising from a use of `op'
Possible fix:
add (DoC (x (A2 (FCon x) -> A3 (FCon x)))) to the context of
the type signature for `fCon'
or add an instance declaration for
(DoC (x (A2 (FCon x) -> A3 (FCon x))))
In the first argument of `foldDoC', namely `op'
In the expression: foldDoC op
In an equation for `fCon': fCon = foldDoC op
......@@ -6,33 +6,33 @@ rebindable6.hs:106:17:
add an instance declaration for (HasSeq (IO a -> t -> IO b))
In a stmt of a 'do' expression: f
In the expression:
do { f;
Just (b :: b) <- g;
return b }
do { f;
Just (b :: b) <- g;
return b }
In an equation for `test_do':
test_do f g
= do { f;
Just (b :: b) <- g;
return b }
= do { f;
Just (b :: b) <- g;
return b }
rebindable6.hs:107:17:
No instances for (HasBind (IO (Maybe b) -> (Maybe b -> t1) -> t),
HasFail ([Prelude.Char] -> t1))
No instances for (HasFail ([Prelude.Char] -> t1),
HasBind (IO (Maybe b) -> (Maybe b -> t1) -> t))
arising from a do statement
Possible fix:
add an instance declaration for
(HasBind (IO (Maybe b) -> (Maybe b -> t1) -> t),
HasFail ([Prelude.Char] -> t1))
(HasFail ([Prelude.Char] -> t1),
HasBind (IO (Maybe b) -> (Maybe b -> t1) -> t))
In a stmt of a 'do' expression: Just (b :: b) <- g
In the expression:
do { f;
Just (b :: b) <- g;
return b }
do { f;
Just (b :: b) <- g;
return b }
In an equation for `test_do':
test_do f g
= do { f;
Just (b :: b) <- g;
return b }
= do { f;
Just (b :: b) <- g;
return b }
rebindable6.hs:108:17:
No instance for (HasReturn (b -> t1))
......@@ -41,6 +41,6 @@ rebindable6.hs:108:17:
In the expression: return b
In a stmt of a 'do' expression: Just (b :: b) <- g
In the expression:
do { f;
Just (b :: b) <- g;
return b }
do { f;
Just (b :: b) <- g;
return b }
tcfail171.hs:9:10:
No instances for (PrintfArg a, PrintfType b)
No instances for (PrintfType b, PrintfArg a)
arising from a use of `printf'
In the expression: printf "0x%x" x
In an equation for `phex': phex x = printf "0x%x" x
Supports Markdown
0% or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment